1997
DOI: 10.4065/72.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Small-Cell Carcinoma of the Lung Manifesting as Acute Hepatic Failure

Abstract: In this report, we describe four cases of small-cell carcinoma of the lung manifesting as acute hepatic failure. These cases were noteworthy for the presence of hepatomegaly and substantially increased serum lactate dehydrogenase and uric acid levels. The ratio of normalized serum lactate dehydrogenase to normalized serum alanine aminotransferase from the 4 cases reported herein (mean +/- SE, 3.63 +/- 1.10) was significantly greater than the ratio obtained from the 12 cases of nonmalignant fulminant hepatic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…In addition, both patients died after a rapidly deteriorating course complicated by multiple organ failure. Previous case reports also show several similarities to the two cases reported herein, including the presence of massive hepatomegaly and an increase in the serum LDH [7][8][9][10][11][12][13] . The diagnosis could only be confirmed at postmortem examination in most of the reported cases also.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…In addition, both patients died after a rapidly deteriorating course complicated by multiple organ failure. Previous case reports also show several similarities to the two cases reported herein, including the presence of massive hepatomegaly and an increase in the serum LDH [7][8][9][10][11][12][13] . The diagnosis could only be confirmed at postmortem examination in most of the reported cases also.…”
Section: Discussionsupporting
confidence: 49%
“…In the two cases reported herein and also the previously reported patients, there was an at least fivefold increase above the normal 7) . It has been suggested that an elevation of the serum LDH can be used as a prognostic indicator in SCLC patients with disturbed liver chemistry with hepatic failure and impending FHF 7) .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The incidence of lymph node metastasis (s s) does not change (P > 0.1), whereas the prevalence of haematogenous metastasis ( ) increased as IMD increased (P = 0.011) need to elicit microvessel development. Such an angiogenesisindependent growth pattern has been observed in tumours in the lungs and in the liver (McGuire et al, 1997;Pezzella et al, 1997). In this way, the angiogenic properties of the primary tumour, reflected in the IMD value, would not necessarily be related to the potential of metastases to expand.…”
Section: Discussionmentioning
confidence: 96%